Organophosphoric Acid Catalyzed Cyclization–Aromatization of 3-Vinylindoles and 2-Vinylpyridines to Access C3N2 Carbazole–Pyridine Frameworks - Jian, Cui; Xiong, Shushu; He, Yong-Ke; Yang, Yu-Ming; Li, Shaoyu (Synlett, 2025)
A practical, organophosphoric acid-catalyzed, two-component cyclization–aromatization reaction of 3-vinylindoles with 2-vinylpyridines has been established for the efficient assembly of various functionalized 1-pyridin-2-yl-9H-carbazole skeletons. This transformation involves an organophosphoric acid-catalyzed [4+2] cycloaddition reaction, together with a tandem oxidative aromatization process. This synthetic methodology, characterized by mild reaction conditions, outstanding functional-group tolerance, and a scalable synthesis capability, has the potential to support in-depth explorations in the fields of materials science and biomedicine.
Keywords: phosphoric acid catalysis; vinylindoles; vinylpyridines; [4+2] cycloaddition; oxidative aromatization; pyridinylcarbazoles